Impact of board structure and firm performance on chief executive's compensation / Mohsin Ali Patel - Patel, Mohsin Ali (Accounting Research Institute (ARI) and UiTM Press, Universiti Teknologi MARA, 2019)
The corporate board usually influences all important decisions of a firm including setting of its long-term goals, developing a corporate strategic policy, as well as hiring and setting the compensation of the chief executive. Moreover, the organization of the board may have a significant effect on the monitoring and governance of the company. This paper analyses the impact of structure of the board and firm performance on chief executive compensation, in an emerging economy context specifically, Pakistan. Chief executive compensation is one of the controversial and sought after topics in research nowadays. Interestingly, the exploration into the topic has found that there is a significant and positive impact of the non-executive directors serving on the corporate boards on the compensation of chief executive. Furthermore, the size of the board has also showed to have a significant and positive impact on the chief executive’s compensation which logically means that the companies in which the boards are larger than the mean size will relatively pay higher to their chief executives. Also it was found that the performance of the firm does not have a statistically significant impact on chief executive compensation. These results have policy implications and are important to corporate stakeholders.